Spatial Attention Modulates Spike Count Correlations and Granger Causality in the Primary Visual Cortex - Hu, Qiyi; Zheng, Zhiyan; Sui, Xiaohong; Li, Liming; Chai, Xinyu; Chen, Yao (Frontiers in Cellular Neuroscience, 2022)
The influence of spatial attention on neural interactions has been revealed even at early visual information processing stages. It resolves the process of competing for sensory information about objects perceived as targets and distractors. However, the attentional modulation of the interaction between pairs of neurons with non-overlapping receptive fields (RFs) is not well known. Here we investigated the activity of neurons that far enough apart in the primary visual cortex (V1) of alert and behaving monkeys who performed a spatial attention task detecting color change. And we compared attentional modulation from the perspective of spike count correlations and Granger causality among simple and complex cells. The attention-related increase in spike count correlations and decrease in Granger causality was found. The results showed that spatial attention only significantly influenced the interactions between rather than within simple and complex cells. Further, we found the attentional modulation of neuronal interactions changed with preferred directions differences between neurons. Thus, we found spatial attention increased the functional communications and competing connectivities when attending to the neurons' RFs, which dramatically impacts between simple and complex cells. Our findings enrich the model of simple and complex cells and further understand the way that attention influence the neurons’ activities.